2014
DOI: 10.1038/srep05637
|View full text |Cite
|
Sign up to set email alerts
|

PEDF and PEDF-derived peptide 44mer protect cardiomyocytes against hypoxia-induced apoptosis and necroptosis via anti-oxidative effect

Abstract: Pigment epithelium-derived factor (PEDF) has many biological activities. But it's not known whether PEDF and its functional peptides could protect against hypoxia-induced cell death and the mechanisms are still unclear. We used cultured H9c2 cells and primary cardiomyocytes to show that apoptosis and necroptosis were significantly increased after hypoxia. Both PEDF and its fuctional peptides 44mer reduced apoptosis and necroptosis rates and inhibited the expression of cleaved caspase 3 and receptor-interacting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 33 publications
4
58
0
Order By: Relevance
“…That study has revealed that PEDF could upregulate SOD, GPx and CAT activities, thus promote clearing of ROS [4]. As this study has demonstrated, PEDF attenuates hypoxia-induced apoptosis and necrosis by restraining MOMP and MPTP opening via PEDF.…”
Section: Discussionmentioning
confidence: 53%
“…That study has revealed that PEDF could upregulate SOD, GPx and CAT activities, thus promote clearing of ROS [4]. As this study has demonstrated, PEDF attenuates hypoxia-induced apoptosis and necrosis by restraining MOMP and MPTP opening via PEDF.…”
Section: Discussionmentioning
confidence: 53%
“…In many cases, segmental functional peptides play part of the biological function similar to their precursor proteins [41][42][43]. We selected 9 protein precursors closely related to cardiomyocyte structure or AMI from the 119 precursor proteins identified, and listed the differentially expressed peptides that were derived from functional domains in these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It is expressed in multiple tissues and exerts diverse physiological activities, for instance blocking angiogenesis and tumor growth, anti-inflammatory and anti-oxidation [12,13,14]. Our previous studies have declared that PEDF inhibits left ventricular remodeling and improves cardiac function in rats with acute myocardial infarction, and PEDF protects against hypoxia-induced apoptosis and necroptosis via an anti-oxidative effect [15,16]. However, it is not known whether PEDF inhibits the activation of the NLRP3 inflammasome to protect against myocardial cell death in hypoxia cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%